n 3 + n 2 + n + 1 1 0 n
Find the sum of all positive integers n such that the above expression is also an integer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If f(n) is to be an integer,
(
n
3
+
n
2
+
n
+
1
)
m
u
s
t
b
e
d
i
v
i
s
i
b
l
e
b
y
2
O
r
5
o
n
l
y
.
n
3
+
n
2
+
n
=
n
(
n
2
+
n
+
1
)
m
u
s
t
e
n
d
i
n
9
.
S
o
n
a
n
d
(
n
2
+
n
+
1
)
m
u
s
t
b
e
o
d
d
.
F
o
r
n
=
1
,
5
,
9
n
3
+
n
2
+
n
w
i
l
l
n
o
t
e
n
d
i
n
9
.
n
=
3
a
n
d
7
m
a
k
e
s
f
(
n
)
a
n
i
n
t
e
g
e
r
.
I will complete this shortly.
Problem Loading...
Note Loading...
Set Loading...
n 3 + n 2 + n + 1 = ( n + 1 ) ( n 2 + 1 ) Note that if n be an even number, then n + 1 and n 2 + 1 will be two odd co-prime numbers, but 1 0 n contains only one odd prime and ( n + 1 ) ( n 2 + 1 ) ∤ 1 0 n . So n must be an odd number. n = 1 is not an answer, suppose n > 1 .
With n odd, n 2 + 1 has an odd divisor since if n = 2 k + 1 then n 2 + 1 = 2 ( 2 k 2 + 2 k + 1 ) and g cd ( n + 1 , n 2 + 1 ) = 2 , It follows that n + 1 = 2 a and n 2 + 1 = 2 × 5 b . Combine to get 2 a ( 2 a − 1 − 1 ) = 5 b − 1 ⋆ So 2 a ∣ 5 b − 1 and power of 2 in 5 b − 1 is a , so using LTE lemma we get 2 + v 2 ( b ) = v 2 ( 5 b − 1 ) = a v 2 ( b ) = a − 2 Let b = 2 a − 2 ( 2 c + 1 ) ; c ≥ 0 , equation ⋆ turns into 2 a ( 2 a − 1 − 1 ) = 5 2 a − 2 ( 2 c + 1 ) − 1 But for a ≥ 4 5 2 a − 2 ( 2 c + 1 ) − 1 = ( 5 2 a − 3 ( 2 c + 1 ) − 1 ) ( 5 2 a − 3 ( 2 c + 1 ) + 1 ) > 8 × 2 a − 3 ( 2 c + 1 ) ( 1 + 8 × 2 a − 3 ( 2 c + 1 ) + 1 ) = 2 a ( 2 c + 1 ) ( 2 a ( 2 c + 1 ) + 2 ) ≥ 2 a ( 2 a + 2 ) > 2 a ( 2 a − 1 − 1 ) using the fact that 5 z > 1 + 8 z for z > 1 . So a < 4 and trying values gives a = 2 , 3 and n = 2 a − 1 = 3 , 7 as answers. For n = 3 and n = 7 the expression ( n + 1 ) ( n 2 + 1 ) indeed divides 1 0 n .